In Search of Popularity: Non-Conforming Reputations of Hispanic Adolescent Graffiti Writers - Ryabov, Igor (Qualitative Sociology Review, 2016)
Although the literature on graffiti writers continues to expand, there is a paucity of studies on Hispanic adolescent writers in the U.S., especially with a focus on assimilation. Using the qualitative analyses of in-depth interviews with Hispanic adolescent writers, this study attempts to fill in the gaps in our understanding of whether and how ethnologies of writers differ with respect to their family-, school-, and peer-related experiences. A key feature of the study is comparison of two crews (groups) of Hispanic adolescent writers who differ with respect to their immigrant generational status. Above all, this paper seeks an understanding of the purpose behind the graffiti-writing behavior. The findings of this study underscore the importance of boundary-testing, status- and risk-seeking in the lives of adolescent writers who, through the engagement in graffiti-writing, attempt to establish a non-conforming reputation among one’s peers.